探讨中国超市经营的最适规模 = An inquiry into optimal supermarket scale in China - 葛磊 Ge, Lei (2008)
The thesis first described the development of the Chinese supermarket, since 1980. The relationship between one-stop purchase and the scale of supermarket was highlighted after reviewing three theoretical considerations on the determination of optimal supermarket scale by Chinese academia. Finally, the determination of optimal scale for single and chain supermarket in 1980s and 1990s were discussed by short-term and long-term cost structure and increase in consumers' demand for supermarket products, preference for shopping in supermarket. It was concluded that the optimal scale of supermarket was increased due to increased income and consumer preference for shopping in supermarket.